Impact of Sex on Long-term Clinical Outcomes After Percutaneous Coronary Intervention. Issue 4 (December 2017) - Ghoreyshi-Hefzabad, Seyed-Mohammad; Kassaian, Seyed-Ebrahim; Kheirkhah-Sabetghadam, Shahrbanoo; Jalali, Arash; Poorhosseini, Hamidreza; Movahed, Mohammad Reza; Nematipour, Ebrahim; Salarifar, Mojtaba; Alidoosti, Mohammad; Ghoreyshi- Hefzabad, Seyedeharezoo; Alaeddini, Farshid; Sadeghian, Saeed; et al.
Abstract : Aims: To evaluate the impact of sex on long-term clinical outcomes after percutaneous coronary intervention (PCI). Methods: In a large prospective cohort, 5664 patients (1716 women and 3948 men) who underwent PCI in a tertiary cardiac center between March 2007 and March 2010 were enrolled. Patients were followed up for median of 74.3 months. We compared the occurrence of long-term mortality, myocardial infarction (MI), and repeated revascularization between 2 sexes. Major adverse cardiac events were defined as a composite end point consisting of occurrence of all-cause mortality, nonfatal MI, or target vessel revascularization during follow-up period. Results: Women were older and had more conventional coronary artery disease risk factors, had smaller vessel diameter, and received drug-eluting stents more frequently than men. On the contrary, men were much more smokers and had higher frequency of acute coronary syndrome, multivessel disease, total coronary occlusion, and lower ejection fraction. After >6 years of follow-up, the all-cause mortality, nonfatal MI, target vessel revascularization, major adverse cardiac events, patient-oriented composite end point, and total repeat PCI were similar between 2 sexes. After adjusting for potential confounders, the total repeat PCI was the only observed difference that was significantly lower in women [11.2% in women vs. 12.4% in men, adjusted subdistributional hazard ratio=0.73 (95% confidence interval, 0.6–0.88); P = 0.001). Conclusions: During >6 years of follow-up, no significant difference was observed in major clinical outcomes between 2 sexes.